Characterization and ex vivo Expansion of Human Placenta-Derived Natural Killer Cells for Cancer Immunotherapy - Zhang, Xiaokui; Kang, Lin; Voskinarian-Berse, Vanessa; Law, Eric; Reddin, Tiffany; Bhatia, Mohit; Hariri, Alexandra; Ning, Yuhong; Dong, David; Maguire, Timothy; Yarmush, Martin; Hofgartner, Wolfgang; et al. (Frontiers in Immunology, 2013)
Recent clinical studies suggest that adoptive transfer of donor-derived natural killer (NK) cells may improve clinical outcome in hematological malignancies and some solid tumors by direct anti-tumor effects as well as by reduction of graft versus host disease (GVHD). NK cells have also been shown to enhance transplant engraftment during allogeneic hematopoietic stem cell transplantation (HSCT) for hematological malignancies. The limited ex vivo expansion potential of NK cells from peripheral blood (PB) or umbilical cord blood (UCB) has however restricted their therapeutic potential. Here we define methods to efficiently generate NK cells from donor-matched, full-term human placenta perfusate (termed Human Placenta-Derived Stem Cell, HPDSC) and UCB. Following isolation from cryopreserved donor-matched HPDSC and UCB units, CD56+CD3− placenta-derived NK cells, termed pNK cells, were expanded in culture for up to 3 weeks to yield an average of 1.2 billion cells per donor that were >80% CD56+CD3−, comparable to doses previously utilized in clinical applications. Ex vivo-expanded pNK cells exhibited a marked increase in anti-tumor cytolytic activity coinciding with the significantly increased expression of NKG2D, NKp46, and NKp44 (p < 0.001, p < 0.001, and p < 0.05, respectively). Strong cytolytic activity was observed against a wide range of tumor cell lines in vitro. pNK cells display a distinct microRNA (miRNA) expression profile, immunophenotype, and greater anti-tumor capacity in vitro compared to PB NK cells used in recent clinical trials. With further development, pNK may represent a novel and effective cellular immunotherapy for patients with high clinical needs and few other therapeutic options.